Implementation Of EMKM SAK In Inventory Recording At ASHER Pharmacy In Fodo Village, South Gunungsitoli District - Wan Riang Zega; Sophia Molinda Kakisina; Noviza Asni Waruwu; Fakta Solala Zebua (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in inventory recording at Asher Pharmacy in Fodo Village, Gunungsitoli South District. SAK EMKM is an accounting standard designed to facilitate small and medium-sized entities in preparing relevant, reliable, and compliant financial statements in accordance with accounting principles applicable in Indonesia. Inventory, as one of the significant current assets in a pharmacy business, requires accurate recording to support managerial decision-making and the preparation of accurate financial statements. This study used a qualitative descriptive method with a case study approach, in which data were obtained through interviews, observations, and documentation of the inventory recording process at Asher Pharmacy. The analysis was conducted by comparing the inventory recording practices applied with the provisions of SAK EMKM, including recognition, measurement, and presentation. The results of the study indicate that inventory recording at Apotek Asher has been carried out systematically, but there are several aspects that are not yet fully in accordance with SAK EMKM, particularly in terms of inventory valuation and disclosure in financial statements. The researcher recommends that Apotek Asher adjust its recording procedures in accordance with standards to improve the reliability of financial information and support more effective business management.